2010
DOI: 10.1111/j.1460-9568.2010.07129.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant fluoxetine suppresses neuronal growth from both vertebrate and invertebrate neurons and perturbs synapse formation between Lymnaea neurons

Abstract: Current treatment regimes for a variety of mental disorders involve various selective serotonin reuptake inhibitors such as Fluoxetine (Prozac). Although these drugs may 'manage' the patient better, there has not been a significant change in the treatment paradigm over the years and neither have the outcomes improved. There is also considerable debate as to the effectiveness of various selective serotonin reuptake inhibitors and their potential side-effects on neuronal architecture and function. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
5
15
0
Order By: Relevance
“…Therefore, a detailed evaluation of the effect of HgCl 2 at these concentrations may still be required. Specially, the effect of HgCl 2 on the motile structure of growth cones, the length of neurite elongation, and cell viability would need to be monitored using proper neuronal model types in which these parameters can be easily measured as shown in our previous study [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a detailed evaluation of the effect of HgCl 2 at these concentrations may still be required. Specially, the effect of HgCl 2 on the motile structure of growth cones, the length of neurite elongation, and cell viability would need to be monitored using proper neuronal model types in which these parameters can be easily measured as shown in our previous study [57]. …”
Section: Discussionmentioning
confidence: 99%
“…These trophic factor-mediated intracellular Ca 2+ oscillations required for excitatory synapse formation were inhibited in the presence of fluoxetine, indicating that fluoxetine prevents the expression of proteins involved in synaptogenesis (Xu et al, 2010). Attesting to this, we found that the expression and synaptic localization of synaptophysin, a synaptic vesicle-associated protein and presynaptic biomarker, were significantly reduced in synapses formed in the presence of fluoxetine, but not citalopram (Getz et al, 2011).…”
Section: Fluoxetine But Not Citalopram Inhibits Synapse Formationmentioning
confidence: 50%
“…To this end, Lymnaea serotonergic or non-serotonergic neurons were cultured under control conditions (in the presence of growth media containing neurotrophic factors), or in the presence of SSRIs over a therapeutically-relevant dosage range. The neuronal ability to initiate and elongate neurite processes, spread branches and form active growth cones was monitored under these two conditions (Xu et al, 2010). We found that neurons cultured in growth media alone established extensive neurite outgrowth (massive branches with active growth cones), while neurons cultured in the presence of fluoxetine exhibited only minimal branches and shorter processes at lower doses (< 3 μg/mL), and no growth at higher concentrations (> 3 μg/mL).…”
Section: Fluoxetine Inhibits the Initiation Of Neurite Outgrowth And mentioning
confidence: 99%
See 2 more Smart Citations